Peningkatan Pendapatan Masyarakat Melalui Penerapan Teknologi Budidaya Cabe di Pekarangan - Shodiq Eko Ariyanto; Nova Laili Wisuda (Muria Jurnal Layanan Masyarakat, 2019)
The high price of chilies will have an impact on family income decreases, therefore to resolve the problem accordingly held a program "Community Participation Movement to Utilize Home Garden for Indonesian Family Food Security". Chilli cultivation in the garden of the house, is expected to meet the needs of food and family nutrition and income increase, which in turn can improve the welfare of the family and able to realize food self-sufficiency at the household level. Society needs motivation to cultivate chilli plants in the garden of the house. This activity aims to provide training and skills to the community about chilli farming techniques in the garden of the house. The method used is to provide material theoretically in Pati Kidul Village, Pati Sub-district, Pati Regency about the development of chilli farming business in the garden. In addition, training and mentoring techniques are also planted in the garden to support society income. The result of the activity of dedication to the community of garden utilization in Pati Kidul Subdistrict Pati Regency, the community is able to develop and implement chilli farming technique in the garden, to increase family income. By planting two rawit chili plants and three red curly pepper plants in the garden per house can save expenses for chili shopping for Rp 15.000, - up to Rp. 20,000, - every month after the crops are in production.